Evaluation of the botulinum toxin effects in the correction of gummy smile 32 weeks after application - Vieira, Carlos Eduardo Alonso (2022)
Introduction: The use of botulinum toxin type A (BTX-A) to correct gummy smile has become popular in recent years. Objective: To evaluate the effects of BTX-A application in the correction of gummy smile 2 and 32 weeks after application. Methods: The sample comprised 35 patients (30 female, 5 male) at a mean age of 25.51 years (±5.59) with gummy smile due to muscular hyperfunction. In each patient, 2U of botulinum toxin was applied in the levator labii superioris alaeque nasi, 2 mm from the nasolabial fold. Photographs of spontaneous smiles were taken at 3 stages: before, 2 and 32 weeks after BTX application. Measurements of the gingival display were performed with the Radioface Studio 2 Software, and the calibration used the actual size of the right maxillary central incisor. Comparison of the three stages evaluated was performed with repeated measures ANOVA and Tukey tests. Results: Gingival display decreased significantly 2 weeks after BTX-A application and increased after 32 weeks but did not return to the initial value. Conclusion: There was a significant improvement in gummy smile 2 weeks after botulinum toxin application, and a significant relapse in the gingival display after 32 weeks, however not returning to baseline values.